Using Group Discussion To Improve The EFL Students' Speaking Skill At Smp-It Darul Muhsin Islamic Boarding School - Apriani, Rini; Maysuroh, Siti; Dwimaulani, Astrid; Surayya, Siti Ayu (LITPAM, 2025)
This study aims to determine the effectiveness of using group discussion to improve EFL students’ speaking skill at SMP-IT Darul Muhsin Islamic Boarding School. The method was chosen because it allows students to share ideas, collaborate, and practice speaking in a more interactive and supportive environment. This research used a pre-experimental quantitative design with a one-group pretest-posttest approach, involving 15 Grade 3 students. Data were collected through pre-test and post-test to measure students’ progress, supported by a questionnaire to identify their perceptions. The finding showed a significant improvement in students’ speaking ability after the treatment, with the mean score increasing from 12.11 to 17.6. The paired sample t-test result (Sig. = 0.000<0.05) indicated that group discussion significantly enhanced their speaking performance. In conclusion, group discussion effectively improved students’ fluency, pronunciation, and vocabulary, while also increasing their confidence and motivation in speaking English. Therefore, it can be considered a suitable and engaging method for developing students’ speaking skills in the EFL classroom.